1999
DOI: 10.1002/(sici)1098-108x(199912)26:4<397::aid-eat5>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

The ups and downs of anorexia nervosa

Abstract: Objective: We updated our incidence study by identifying Rochester, Minnesota, residents diagnosed with anorexia nervosa during 1985 through 1989. Method: From a community-based epidemiologic resource, 2,806 medical records with diagnoses including anorexia nervosa, eating disorder, bulimia, amenorrhea and other conditions were screened to identify new cases of anorexia nervosa. Results: Two hundred eight (193 females and 15 males) residents fulfilled standard diagnostic criteria for anorexia nervosa. The over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 0 publications
4
35
1
6
Order By: Relevance
“…Furthermore, the affected age of anorexia nervosa patients overlaps with the period of peak bone formation. The risk of lifetime fracture in anorexia nervosa patients is about 2·9 times the norm (Lucas et al 1999).…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Furthermore, the affected age of anorexia nervosa patients overlaps with the period of peak bone formation. The risk of lifetime fracture in anorexia nervosa patients is about 2·9 times the norm (Lucas et al 1999).…”
Section: Introductionmentioning
confidence: 74%
“…Especially in anorexia nervosa, estrogen deficiency is one of the contributing factors, because the degree of bone loss is directly correlated with the duration of amenorrhea (Biller et al 1989). Hypercortisolism, present in about 22% of patients, can also accelerate bone loss (Lucas et al 1999). Another worrisome problem might be an increase in the PTH concentration during food restriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were replicated by Lucas et al (1999) using updated incidence rates, and adding the new cases diagnosed with AN from 1985 through 1989. The upward trend in incidence rates was still observed in adolescents 15-to 19-year-old, as well as a noted rise among 10-to 14-year-old females between 1950 and 1989.…”
Section: Indicators Of An Increase Of Anmentioning
confidence: 99%
“…A comparative analysis of the previous 50 years' research has revealed continuance of the linear increase for 15 to 24-year-old females, possibly because of the vulnerability of this age group to social and psychological pressures (Lucas et al, 1999). In 1985 the estimated prevalence of AN among 15 to 19-year-old girls in Rochester was 0.48% (Lucas et al, 1991).…”
Section: Indicators Of An Increase Of Anmentioning
confidence: 99%